PSYCHOSOCIAL FACTORS ASSOCIATED WITH EXCLUSIVE BREASTFEEDING IN POSTPARTUM MOTHERS AT CITRA ARAFIQ HOSPITAL - Alnov, Keyla Aulia; Sholihat, Siti (Klabat Journal of Nursing, 2025)
Exclusive breastfeeding is essential for infant growth and immunity, yet its implementation remains suboptimal. Psychosocial factors, particularly maternal anxiety and perceived social support, are believed to influence breastfeeding behavior. This study aimed to examine the relationship between anxiety and social support with exclusive breastfeeding among postpartum mothers. A cross-sectional analytical study was conducted involving 120 postpartum mothers at Citra Arafiq Hospital, Depok. Samples were selected using purposive sampling. Anxiety was measured using the Zung Self-Rating Anxiety Scale (SAS/ SRAS), and social support was evaluated using the Multidimensional Scale of Perceived Social Support (MSPSS). To analyze the data, the Spearman rank correlation test was used. The results showed a strong negative connection between anxiety and exclusive breastfeeding (ρ = 0.000; r = -0.577), the term negative indicates the opposite direction of the relationship, while strong indicates that the relationship is significant or has a major impact. It means that people with higher anxiety were less likely to exclusively breastfeed. Conversely, a significant positive correlation was found between social support and exclusive breastfeeding (ρ = 0.000; r = -0.487), suggesting that greater support increases the likelihood of successful exclusive breastfeeding. In conclusion, maternal anxiety and social support are significantly associated with exclusive breastfeeding practices. These findings highlight the need for comprehensive postpartum care that includes emotional support and anxiety reduction interventions to improve breastfeeding outcomes. Menyusui eksklusif sangat penting untuk pertumbuhan dan kekebalan bayi, namun implementasinya masih belum optimal. Faktor psikososial, terutama kecemasan ibu dan dukungan sosial yang dirasakan, diyakini mempengaruhi perilaku menyusui. Studi ini bertujuan untuk mengeksplorasi hubungan antara kecemasan dan dukungan sosial dengan menyusui eksklusif di kalangan ibu pasca persalinan. Studi analitis transversal dilakukan melibatkan 120 ibu pasca persalinan di Rumah Sakit Citra Arafiq, Depok. Sampel dipilih menggunakan metode sampling purposif. Kecemasan diukur menggunakan Skala Kecemasan Self-Rating Zung (SAS/SRAS), sedangkan dukungan sosial dievaluasi menggunakan Skala Dukungan Sosial Multidimensi (MSPSS). Untuk menganalisis data, digunakan uji korelasi rank Spearman. Hasil menunjukkan hubungan negatif yang kuat antara kecemasan dan pemberian ASI eksklusif (ρ = 0.000; r = -0.577), istilah negatif menunjukkan arah hubungan yang berlawanan, sedangkan kuat menunjukkan bahwa hubungan tersebut berpengaruh besar atau signifikan. Hal ini berarti orang dengan kecemasan yang lebih tinggi cenderung kurang mungkin melakukan pemberian ASI eksklusif. Sebaliknya, ditemukan korelasi positif yang signifikan antara dukungan sosial dan pemberian ASI eksklusif (ρ = 0.000; r = -0.487), menunjukkan bahwa dukungan yang lebih besar meningkatkan kemungkinan keberhasilan pemberian ASI eksklusif. Kesimpulannya, kecemasan ibu dan dukungan sosial memiliki hubungan yang signifikan dengan praktik menyusui eksklusif. Temuan ini menyoroti pentingnya perawatan pasca persalinan yang komprehensif, yang mencakup dukungan emosional dan intervensi untuk mengurangi kecemasan, guna meningkatkan hasil menyusui.